A thermal insulation and energy-saving material for building

By modifying bamboo fiber composite rigid polyurethane foam, the modified sodium lignin sulfonate reacts with dimethyl methyl phosphonate hybrid nanosilica sol with isocyanate, the problems of fast combustion speed of polyurethane foam materials and insufficient energy-saving and environmentally friendly raw materials are solved, and the flame retardant, heat insulation and compressive effects of the material are achieved.

CN119060555BActive Publication Date: 2025-04-18龙陵中基新型建材有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411083947.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-28
Publication Date
2025-04-18
Estimated Expiration
2043-12-28

AI Technical Summary

Technical Problem

The existing polyurethane foam materials burn fast and release highly toxic gases, and the raw materials are not energy-saving and environmentally friendly, which limits their application in the engineering field.

Method used

It is made by reacting modified bamboo fiber composite rigid polyurethane foam by reacting modified sodium lignin sulfonate with dimethyl methylphosphonate hybrid nanosilica sol with isocyanate, which increases the flame retardant performance and heat insulation effect of the material.

Benefits of technology

The flame retardant, heat insulation and compressive resistance of the material are achieved, the combustion speed and the release of toxic smoke are slowed down, and the green and environmental protection and energy-saving performance of the material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a heat-insulating and energy-saving material for building, and relates to the technical field of building materials. The invention utilizes modified sodium lignin sulfonate and isocyanate to generate rigid polyurethane foam, which can form an expanded, continuous and dense carbon layer under high temperature conditions, so that the matrix can achieve flame retardant and heat-insulating effects, and in the foaming process, dimethyl methylphosphonate hybrid nano silica sol is added to achieve strong compressive resistance and heat-insulating performance, and dimethyl methylphosphonate can synergistically act with silica to isolate the entry of external oxygen, thereby increasing the flame retardant and heat-insulating effects of the material; then, modified cellulose nanofibers are grafted on the surface of bamboo fibers to form a solid three-dimensional network structure in the rigid polyurethane foam matrix, and the hollow porous structure of the bamboo fiber cell wall is added to increase the compressive and heat-insulating effects of the polyurethane material. The material prepared by the invention has flame retardant, heat-insulating and compressive resistance effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to a thermal insulation and energy-saving material for buildings. Background Art

[0002] my country is currently the world's largest construction market, and polyurethane has entered the public eye. Due to its excellent physical and mechanical properties, electrical properties, acoustic properties and chemical corrosion resistance, and its strong adhesion to a variety of materials, it is widely used as a thermal insulation material for petrochemical pipelines, refrigeration equipment, transportation equipment and buildings. However, since polyurethane foam burns too quickly and releases highly toxic gases, it is considered one of the main causes of heavy casualties. In addition, the raw materials of polyurethane, polyether polyols and isocyanates, are petroleum-based, not energy-saving and environmentally friendly, and are non-renewable, which greatly limits their application in the engineering field. Lignin is the second largest renewable resource in nature after cellulose, and its molecular chain contains abundant hydroxyl groups, which provides the possibility for lignin to replace polyurethane raw material polyether polyols. Combined with new flame retardants, the flame retardant properties of polyurethane are improved and the highly toxic gases produced by combustion are suppressed, making it suitable for practical applications, which is of great significance to promoting the development of green, environmentally friendly and energy-saving buildings. Summary of the invention

[0003] The object of the present invention is to provide a thermal insulation and energy-saving material for construction and a preparation method thereof, so as to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a thermal insulation and energy-saving material for building, wherein the thermal insulation and energy-saving material for building is made of modified bamboo fiber composite rigid polyurethane foam.

[0005] Furthermore, the rigid polyurethane foam is prepared by reacting modified sodium lignin sulfonate mixed with dimethyl methylphosphonate hybrid nano-silica sol and isocyanate.

[0006] Furthermore, the modified sodium lignin sulfonate is prepared by modifying sodium lignin sulfonate with formaldehyde under alkaline conditions.

[0007] Furthermore, the modified bamboo fiber is prepared by first treating the bamboo fiber with sodium hydroxide and then grafting the modified cellulose nanofiber.

[0008] Furthermore, the modified cellulose nanofibers are prepared from cellulose nanofibers modified by silane coupling agent KH560.

[0009] Furthermore, a method for preparing a thermal insulation and energy-saving material for construction includes the following preparation steps:

[0010] (1) A 20wt% sodium lignin sulfonate aqueous solution was mixed with anhydrous ethanol in a mass ratio of 1:5, stirred at 70-100rpm for 1-2h, allowed to stand for 24h, filtered, the solid was taken, and dried at 70°C for 4-6h to obtain refined sodium lignin sulfonate; refined sodium lignin sulfonate, formaldehyde, and deionized water were mixed in a mass ratio of 3:0.8:12-7:1.2:20, 10wt% sodium hydroxide solution was added until the solution pH was 12, distilled at 70-100°C for 4-6h, cooled to room temperature, and vacuum dried at 60-70°C for 3-6h to obtain modified sodium lignin sulfonate;

[0011] (2) Heat dimethyl methylphosphonate, deionized water, ethanol, and ammonia water to 80°C, stir at 70-100 rpm for 30-60 min, add ethyl orthosilicate, react for 20-30 h, add silane coupling agent KH570, react at 70-100°C for 1-4 h, and obtain dimethyl methylphosphonate hybrid nano-silica sol;

[0012] (3) Soak the bamboo fiber in a 4wt% sodium hydroxide solution with a mass of 10 to 15 times that of the bamboo fiber, heat it to 60 to 90°C, stir it at 70 to 100 rpm for 80 to 120 min, let it stand for 10 to 14 h, wash it with distilled water for 8 to 10 times, filter it, take the solid, vacuum dry it at 50 to 70°C for 10 to 15 h, add distilled water with a mass of 30 to 40 times that of the bamboo fiber, sodium chlorite with a mass of 0.28 to 0.42 times that of the bamboo fiber, and glacial acetic acid with a mass of 0.18 to 0.35 times that of the bamboo fiber, heat it to 70 to 80°C, let it stand for 50 to 80 min, wash it with distilled water for 5 to 10 times, and dry it at 20 to 40°C for 10 to 15 h to obtain the pretreated bamboo fiber;

[0013] (4) Anhydrous ethanol, silane coupling agent KH560, and distilled water were mixed in a mass ratio of 35:3:0.8-43:5:1.2, stirred at 1000-1500 rpm for 15-25 min, 0.8-1.2 times the mass of silane coupling agent KH560 in cellulose nanofiber emulsion was added, and stirred at 1200-1800 rpm for 15-25 min to obtain a modified cellulose nanofiber mixed solution;

[0014] (5) spraying the modified cellulose nanofiber mixed solution at 40 g / m2 uniformly on the pretreated bamboo fiber, and drying at 50-70°C for 4-6 h to obtain the modified bamboo fiber;

[0015] (6) Dibutyltin dilaurate, dimethyl methylphosphonate hybrid nano-silica sol, modified sodium lignin sulfonate and modified bamboo fiber are mixed, stirred at 70-100 rpm for 20-40 min, diphenylmethane diisocyanate is added, stirring is continued for 1-3 min, poured into a mold, allowed to stand for 60-90 min, demolded, and aged at 50-80°C for 8-12 h to obtain a thermal insulation and energy-saving material for construction.

[0016] Furthermore, the vacuum degree in step (1) and step (3) is both 0.2-1 kPa.

[0017] Furthermore, in step (2), the mass ratio of dimethyl methylphosphonate, deionized water, ethanol, aqueous ammonia, tetraethyl orthosilicate, and silane coupling agent KH570 is 3:5:3.5:0.3:4:0.01-7:10:5:0.8:9:0.05.

[0018] Furthermore, the preparation method of the cellulose nanofiber emulsion in step (4) is as follows: N-methylpyrrolidone, dimethylolpropionic acid, isophorone diisocyanate and dibutyltin dilaurate are mixed in a mass ratio of 1:0.6:0.3:0.1-1:0.8:0.5:0.2, heated to 40-50°C, reacted for 1-3 hours, and obtained a mixed solution; cellulose nanofibers are dissolved in a 20% butanone aqueous solution with a mass fraction of 4-8 times the mass of the cellulose nanofibers, heated to 70-80°C, reacted for 2-3 hours, cooled to 35-45°C, added with a mixed solution with a mass fraction of 2-3 times the mass of the cellulose nanofibers and triethylamine with a mass fraction of 1.5-2.5 times the mass of the cellulose nanofibers, reacted for 30-60 minutes, cooled to 15-25°C, added with deionized water with a mass fraction of 4-6 times the mass of the cellulose nanofibers, and stirred at 1200-1500 rpm for 20-40 minutes.

[0019] Furthermore, in step (6), the mass ratio of dibutyltin dilaurate, dimethyl methylphosphonate hybrid nano-silica sol, modified sodium lignin sulfonate, modified bamboo fiber, and diphenylmethane diisocyanate is 1:11:20:4.5:20~2:15:25:6:25.

[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0021] The building material of the invention is prepared by composite rigid polyurethane foam with modified bamboo fiber to achieve the effects of flame retardancy, heat insulation and pressure resistance.

[0022] Firstly, the invention activates and modifies sodium lignin sulfonate, introduces hydroxymethyl to the ortho position of phenolic hydroxyl by formaldehyde under alkaline conditions, and undergoes cross-linking reaction with isocyanate to generate polyurethane, and under high temperature conditions, hydroxyl and benzene ring in lignin undergo carbon chain rearrangement to generate a large amount of residual carbon to undergo esterification reaction, dehydration and cross-linking to form an expanded, continuous and dense carbon layer, which effectively isolates the transfer of air and heat, thereby inhibiting the combustion and protecting the internal materials, so that the matrix achieves flame retardant and heat insulation effects; then, the phosphorus oxygen double bond in dimethyl methylphosphonate is hydrogen-bonded with the silicon hydroxyl group on silicon dioxide to form dimethyl methylphosphonate hybrid nano-silica sol, wherein dimethyl methylphosphonate has amphiphilicity and nano-silica has a three-dimensional nanostructure, and the two The dispersion of the above-mentioned dimethyl methylphosphonate in the polyurethane material can not only improve the compatibility of sodium lignin sulfonate and increase the hard segment content in the foam, but also fill the polyurethane foam pores to form a high-temperature barrier layer and increase its density, thereby achieving a strong compressive resistance and enhancing the thermal insulation performance of the matrix. Moreover, when the material is burned, a part of the phosphorus-containing groups of dimethyl methylphosphonate can decompose to form a non-volatile phosphoric acid liquid protective film, and with the assistance of nano-silicon dioxide, it can greatly isolate the entry of external oxygen. The other part of the phosphorus-containing free radicals can capture the hydrogen ions and hydroxide ions generated during the combustion and degradation process, forcing the chain reaction of the free radicals to be interrupted, effectively terminating the combustion reaction, thereby slowing down the combustion rate of the polyurethane material and the release of toxic smoke, and enhancing the flame retardant and thermal insulation effects of the material.

[0023] Secondly, the hydroxyl groups in the alkaline solution are used to partially untwist the fibrils in the fibers, thereby removing the colloidal hemicellulose on the surface of the bamboo fibers, exposing and refining the cellulose, increasing the contact area with the matrix, enhancing the adhesion between the bamboo fibers and the material, and forming a three-dimensional network structure therein. At the same time, the cellulose nanofibers are modified and grafted onto the surface of the bamboo fibers through the coupling agent KH560, effectively filling the gaps between the interface of the bamboo fibers and the matrix, reinforcing the three-dimensional structure, making the composite material more compact and improving its compressive resistance. The isocyanate group reacts and couples with the hydroxyl groups on the surface of the bamboo fibers and penetrates into the polyurethane. At the same time, the cell wall of the bamboo fibers has a hollow and porous structure, which enhances the thermal insulation effect of the material. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the thermal insulation and energy-saving materials for buildings prepared in the following examples are as follows:

[0026] Thermal insulation: Take the embodiment and comparative example of the same size and conduct thermal conductivity test with reference to GB / T10294 "Thermal conductivity / thermal conductivity and thermal resistance test of thermal insulation materials".

[0027] Compression resistance: Take the embodiment and comparative example of the same size and perform compressive strength test with reference to GB / T5486 "Test methods for inorganic rigid thermal insulation products".

[0028] Flame retardancy: The embodiment and the comparative example of the same size were taken and subjected to UL94 horizontal and vertical burning test and material LOI test according to GB / T2408 and GB / T2406.2 standards.

[0029] Example 1

[0030] (1) A 20 wt% sodium lignin sulfonate aqueous solution was mixed with anhydrous ethanol in a mass ratio of 1:5, stirred at 70 rpm for 1 h, allowed to stand for 24 h, filtered, the solid was taken, and dried at 70 ° C for 4 h to obtain refined sodium lignin sulfonate; refined sodium lignin sulfonate, formaldehyde, and deionized water were mixed in a mass ratio of 3:0.8:12, 10 wt% sodium hydroxide solution was added until the solution pH was 12, distilled at 70 ° C for 4 h, cooled to room temperature, and dried at 60 ° C and a vacuum degree of 0.2 kPa for 3 h to obtain modified sodium lignin sulfonate;

[0031] (2) heating dimethyl methylphosphonate, deionized water, ethanol, and ammonia water to 80°C, stirring at 70 rpm for 30 min, adding tetraethyl orthosilicate, reacting for 20 h, adding silane coupling agent KH570, and reacting at 70°C for 1 h to obtain dimethyl methylphosphonate hybrid nano-silica sol; the mass ratio of dimethyl methylphosphonate, deionized water, ethanol, ammonia water, tetraethyl orthosilicate, and silane coupling agent KH570 is 3:5:3.5:0.3:4:0.01;

[0032] (3) The bamboo fiber was immersed in a 4wt% sodium hydroxide solution with a mass of 10 times that of the bamboo fiber, heated to 60°C, stirred at 70rpm for 80min, allowed to stand for 10h, washed with distilled water for 8 times, filtered, and the solid was dried at 50°C and a vacuum degree of 0.2kPa for 10h. Distilled water with a mass of 30 times that of the bamboo fiber, sodium chlorite with a mass of 0.28 times that of the bamboo fiber, and glacial acetic acid with a mass of 0.18 times that of the bamboo fiber were added, heated to 70°C, allowed to stand for 50min, washed with distilled water for 5 times, and dried at 20°C for 10h to obtain the pretreated bamboo fiber.

[0033] (4) N-methylpyrrolidone, dimethylolpropionic acid, isophorone diisocyanate and dibutyltin dilaurate were mixed in a mass ratio of 1:0.6:0.3:0.1, heated to 40°C, and reacted for 1 hour to obtain a mixed solution; cellulose nanofibers were dissolved in a 20% butanone aqueous solution with a mass fraction of 4 times the mass of the cellulose nanofibers, heated to 70°C, reacted for 2 hours, cooled to 35°C, and the mixed solution with a mass fraction of 2 times the mass of the cellulose nanofibers and triethylamine with a mass fraction of 1.5 times the mass of the cellulose nanofibers were added. After reacting for 30 minutes, the temperature was lowered to 15°C, deionized water of 4 times the mass of cellulose nanofibers was added, and the mixture was stirred at 1200 rpm for 20 minutes to obtain a cellulose nanofiber emulsion; anhydrous ethanol, silane coupling agent KH560, and distilled water were mixed in a mass ratio of 35:3:0.8, and stirred at 1000 rpm for 15 minutes, and a cellulose nanofiber emulsion of 0.8 times the mass of silane coupling agent KH560 was added, and stirred at 1200 rpm for 15 minutes to obtain a modified cellulose nanofiber mixed solution;

[0034] (5) spraying the modified cellulose nanofiber mixed solution evenly on the pretreated bamboo fiber at a concentration of 40 g / m2, and drying at 50°C for 4 h to obtain the modified bamboo fiber;

[0035] (6) Dibutyltin dilaurate, dimethyl methylphosphonate hybrid nano-silica sol, modified sodium lignin sulfonate, and modified bamboo fiber are mixed, stirred at 70 rpm for 20 min, diphenylmethane diisocyanate is added, and stirring is continued for 1 min. The mixture is poured into a mold, allowed to stand for 60 min, demolded, and aged at 50° C. for 8 h to obtain a thermal insulation and energy-saving material for construction; the mass ratio of the dibutyltin dilaurate, dimethyl methylphosphonate hybrid nano-silica sol, modified sodium lignin sulfonate, modified bamboo fiber, and diphenylmethane diisocyanate is 1:11:20:4.5:20.

[0036] Example 2

[0037] (1) A 20 wt% sodium lignin sulfonate aqueous solution was mixed with anhydrous ethanol in a mass ratio of 1:5, stirred at 85 rpm for 1.5 h, allowed to stand for 24 h, filtered, the solid was taken, and dried at 70 ° C for 5 h to obtain refined sodium lignin sulfonate; refined sodium lignin sulfonate, formaldehyde, and deionized water were mixed in a mass ratio of 5:1:16, 10 wt% sodium hydroxide solution was added until the solution pH was 12, distilled at 85 ° C for 5 h, cooled to room temperature, and dried at 65 ° C and a vacuum degree of 0.6 kPa for 4.5 h to obtain modified sodium lignin sulfonate;

[0038] (2) heating dimethyl methylphosphonate, deionized water, ethanol, and ammonia water to 80°C, stirring at 85 rpm for 45 min, adding tetraethyl orthosilicate, reacting for 25 h, adding silane coupling agent KH570, and reacting at 85°C for 3 h to obtain dimethyl methylphosphonate hybrid nano-silica sol; the mass ratio of dimethyl methylphosphonate, deionized water, ethanol, ammonia water, tetraethyl orthosilicate, and silane coupling agent KH570 is 5:8:4:0.6:6.5:0.03;

[0039] (3) The bamboo fiber was immersed in a 4wt% sodium hydroxide solution with a mass of 13 times that of the bamboo fiber, heated to 75°C, stirred at 85rpm for 100min, allowed to stand for 12h, washed with distilled water for 9 times, filtered, and the solid was dried at 60°C and a vacuum degree of 0.6kPa for 13h. Distilled water with a mass of 35 times that of the bamboo fiber, sodium chlorite with a mass of 0.35 times that of the bamboo fiber, and glacial acetic acid with a mass of 0.28 times that of the bamboo fiber were added, heated to 75°C, allowed to stand for 65min, washed with distilled water for 8 times, and dried at 30°C for 12.5h to obtain the pretreated bamboo fiber;

[0040] (4) N-methylpyrrolidone, dimethylolpropionic acid, isophorone diisocyanate and dibutyltin dilaurate were mixed in a mass ratio of 1:0.7:0.4:0.15, heated to 45°C, and reacted for 2 hours to obtain a mixed solution; cellulose nanofibers were dissolved in a 20% butanone aqueous solution with a mass fraction of 6 times the mass of the cellulose nanofibers, heated to 75°C, reacted for 2.5 hours, cooled to 40°C, and the mixed solution with a mass fraction of 2.5 times the mass of the cellulose nanofibers and a 20% butanone aqueous solution with a mass fraction of 2 times the mass of the cellulose nanofibers were added; triethylamine, react for 45 minutes, cool to 20°C, add deionized water 5 times the mass of cellulose nanofibers, stir at 1350rpm for 30 minutes to obtain cellulose nanofiber emulsion; mix anhydrous ethanol, silane coupling agent KH560 and distilled water in a mass ratio of 40:4:1, stir at 1200rpm for 20 minutes, add cellulose nanofiber emulsion 1 times the mass of silane coupling agent KH560, stir at 1500rpm for 20 minutes to obtain a modified cellulose nanofiber mixed solution;

[0041] (5) spraying the modified cellulose nanofiber mixed solution evenly on the pretreated bamboo fiber at a concentration of 40 g / m2, and drying at 60°C for 5 h to obtain the modified bamboo fiber;

[0042] (6) Dibutyltin dilaurate, dimethyl methylphosphonate hybrid nano-silica sol, modified sodium lignin sulfonate, and modified bamboo fiber were mixed, stirred at 85 rpm for 30 min, diphenylmethane diisocyanate was added, and stirring was continued for 2 min. The mixture was poured into a mold, allowed to stand for 75 min, demolded, and aged at 65° C. for 10 h to obtain a thermal insulation and energy-saving material for construction; the mass ratio of the dibutyltin dilaurate, dimethyl methylphosphonate hybrid nano-silica sol, modified sodium lignin sulfonate, modified bamboo fiber, and diphenylmethane diisocyanate was 1.5:14:24:5.7:24.

[0043] Example 3

[0044] (1) A 20 wt% sodium lignin sulfonate aqueous solution was mixed with anhydrous ethanol in a mass ratio of 1:5, stirred at 100 rpm for 2 h, allowed to stand for 24 h, filtered, the solid was taken, and dried at 70 ° C for 6 h to obtain refined sodium lignin sulfonate; refined sodium lignin sulfonate, formaldehyde, and deionized water were mixed in a mass ratio of 7:1.2:20, 10 wt% sodium hydroxide solution was added until the solution pH was 12, distilled at 100 ° C for 6 h, cooled to room temperature, and dried at 70 ° C and a vacuum degree of 1 kPa for 6 h to obtain modified sodium lignin sulfonate;

[0045] (2) heating dimethyl methylphosphonate, deionized water, ethanol, and ammonia water to 80°C, stirring at 100 rpm for 60 min, adding tetraethyl orthosilicate, reacting for 30 h, adding silane coupling agent KH570, and reacting at 100°C for 4 h to obtain dimethyl methylphosphonate hybrid nano-silica sol; the mass ratio of dimethyl methylphosphonate, deionized water, ethanol, ammonia water, tetraethyl orthosilicate, and silane coupling agent KH570 is 7:10:5:0.8:9:0.05;

[0046] (3) The bamboo fiber was immersed in a 4wt% sodium hydroxide solution with a mass of 15 times that of the bamboo fiber, heated to 90°C, stirred at 100rpm for 120min, allowed to stand for 14h, washed with distilled water 10 times, filtered, and the solid was dried at 70°C and a vacuum degree of 1kPa for 15h. Distilled water with a mass of 40 times that of the bamboo fiber, sodium chlorite with a mass of 0.42 times that of the bamboo fiber, and glacial acetic acid with a mass of 0.35 times that of the bamboo fiber were added, the temperature was raised to 80°C, allowed to stand for 80min, washed with distilled water 10 times, and dried at 40°C for 15h to obtain the pretreated bamboo fiber.

[0047] (4) N-methylpyrrolidone, dimethylolpropionic acid, isophorone diisocyanate and dibutyltin dilaurate were mixed in a mass ratio of 1:0.8:0.5:0.2, heated to 50°C, and reacted for 3 hours to obtain a mixed solution; cellulose nanofibers were dissolved in a 20% butanone aqueous solution with a mass fraction of 8 times the mass of the cellulose nanofibers, heated to 80°C, reacted for 3 hours, cooled to 45°C, and the mixed solution with a mass fraction of 3 times the mass of the cellulose nanofibers and triethylamine with a mass fraction of 2.5 times the mass of the cellulose nanofibers were added. After reacting for 60 minutes, the temperature was lowered to 25°C, and deionized water of 6 times the mass of cellulose nanofibers was added, and stirred at 1500rpm for 40 minutes to obtain cellulose nanofiber emulsion; anhydrous ethanol, silane coupling agent KH560, and distilled water were mixed in a mass ratio of 43:5:1.2, and stirred at 1500rpm for 25 minutes, and cellulose nanofiber emulsion of 1.2 times the mass of silane coupling agent KH560 was added, and stirred at 1800rpm for 25 minutes to obtain a modified cellulose nanofiber mixed solution;

[0048] (5) spraying the modified cellulose nanofiber mixed solution evenly on the pretreated bamboo fiber at a concentration of 40 g / m2, and drying at 70°C for 6 h to obtain the modified bamboo fiber;

[0049] (6) Dibutyltin dilaurate, dimethyl methylphosphonate hybrid nano-silica sol, modified sodium lignin sulfonate, and modified bamboo fiber are mixed, stirred at 100 rpm for 40 min, diphenylmethane diisocyanate is added, stirring is continued for 3 min, poured into a mold, allowed to stand for 90 min, demolded, and aged at 80° C. for 12 h to obtain a thermal insulation and energy-saving material for construction; the mass ratio of the dibutyltin dilaurate, dimethyl methylphosphonate hybrid nano-silica sol, modified sodium lignin sulfonate, modified bamboo fiber, and diphenylmethane diisocyanate is 2:15:25:6:25.

[0050] Comparative Example 1

[0051] The difference between Comparative Example 1 and Example 2 is that step (1) is omitted, and step (6) is changed to: dibutyltin dilaurate, dimethyl methylphosphonate hybrid nano-silica sol, polyether polyol, and modified bamboo fiber are mixed, stirred at 85 rpm for 30 min, diphenylmethane diisocyanate is added, and stirring is continued for 2 min, poured into a mold, allowed to stand for 75 min, demolded, and aged at 65° C. for 10 h to obtain a thermal insulation and energy-saving material for construction; the mass ratio of dibutyltin dilaurate, dimethyl methylphosphonate hybrid nano-silica sol, polyether polyol, modified bamboo fiber, and diphenylmethane diisocyanate is 1.5:14:24:5.7:24; and the remaining steps are the same as in Example 2.

[0052] Comparative Example 2

[0053] The difference between Comparative Example 2 and Example 2 is that there is no step (2), and step (6) is changed to: dibutyltin dilaurate, modified sodium lignin sulfonate, and modified bamboo fiber are mixed, stirred at 85 rpm for 30 minutes, diphenylmethane diisocyanate is added, and stirring is continued for 2 minutes. The mixture is poured into a mold, allowed to stand for 75 minutes, demolded, and aged at 65° C. for 10 hours to obtain a thermal insulation and energy-saving material for construction; the mass ratio of dibutyltin dilaurate, modified sodium lignin sulfonate, modified bamboo fiber, and diphenylmethane diisocyanate is 1.5:24:5.7:24; and the remaining steps are the same as those in Example 2.

[0054] Comparative Example 3

[0055] The difference between Comparative Example 3 and Example 2 is that there is no step (4) and (5), and step (6) is changed to: dibutyltin dilaurate, dimethyl methylphosphonate hybrid nano-silica sol, modified sodium lignin sulfonate, and pretreated bamboo fiber are mixed, stirred at 85 rpm for 30 minutes, diphenylmethane diisocyanate is added, and stirring is continued for 2 minutes. The mixture is poured into a mold, allowed to stand for 75 minutes, demolded, and aged at 65° C. for 10 hours to obtain a thermal insulation and energy-saving material for construction; the mass ratio of the dibutyltin dilaurate, dimethyl methylphosphonate hybrid nano-silica sol, modified sodium lignin sulfonate, pretreated bamboo fiber, and diphenylmethane diisocyanate is 1.5:14:24:5.7:24; and the remaining steps are the same as in Example 2.

[0056] Comparative Example 4

[0057] The difference between Comparative Example 4 and Example 2 is that there is no step (3) to (5), and step (6) is changed to: dibutyltin dilaurate, dimethyl methylphosphonate hybrid nano-silica sol, and modified sodium lignin sulfonate are mixed, stirred at 85 rpm for 30 minutes, diphenylmethane diisocyanate is added, and stirring is continued for 2 minutes. The mixture is poured into a mold, allowed to stand for 75 minutes, demolded, and aged at 65° C. for 10 hours to obtain a thermal insulation and energy-saving material for construction; the mass ratio of the dibutyltin dilaurate, dimethyl methylphosphonate hybrid nano-silica sol, modified sodium lignin sulfonate, and diphenylmethane diisocyanate is 1.5:14:24:24; and the remaining steps are the same as those in Example 2.

[0058] Effect example

[0059] Table 1 below shows the performance analysis results of the thermal insulation and energy-saving building materials using Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.

[0060] Table 1

[0061]

[0062] From the comparison of the thermal conductivity and flame retardant test results of the embodiment and the comparative example in Table 1, it can be found that the rigid polyurethane foam prepared by reacting sodium lignin sulfonate mixed with dimethyl methylphosphonate hybrid nano-silica sol and diphenylmethane diisocyanate can form an expanded, continuous and dense carbon layer in a high temperature environment, effectively isolating the transfer of air and heat, so that the matrix can achieve flame retardant and heat insulation effects; wherein the phosphorus oxygen double bond in dimethyl methylphosphonate is hydrogen bonded with the silanol group on the silica and dispersed in the polyurethane material, which can not only improve the compatibility of sodium lignin sulfonate, thereby increasing the hard segment content in the foam, but also fill the polyurethane. Ester pores form a high-temperature barrier layer, which increases its density, thereby achieving strong compressive resistance and enhancing the thermal insulation performance of the matrix, and dimethyl methylphosphonate can synergize with nano-silicon dioxide to isolate the entry of external oxygen, thereby enhancing the flame retardant and thermal insulation effects of the material; from the comparison of the compressive strength test data of the embodiment and the comparative example, it can be found that the use of modified cellulose nanofibers grafted on bamboo fibers can effectively fill the gaps between the bamboo fibers and the matrix interface, strengthen the three-dimensional network structure, thereby making the composite material more dense and improving the compressive resistance; at the same time, the bamboo fiber cell wall has a hollow and porous structure, which enhances the thermal insulation effect of the material.

[0063] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A thermal insulation and energy-saving material for building, characterized in that: The thermal insulation and energy-saving material for construction is prepared by composite rigid polyurethane foam with modified bamboo fiber; the preparation method of the thermal insulation and energy-saving material for construction comprises the following preparation steps: (1) A 20 wt% sodium lignin sulfonate aqueous solution was mixed with anhydrous ethanol in a mass ratio of 1:5, stirred at 85 rpm for 1.5 h, allowed to stand for 24 h, filtered, the solid was taken, and dried at 70 ° C for 5 h to obtain refined sodium lignin sulfonate; refined sodium lignin sulfonate, formaldehyde, and deionized water were mixed in a mass ratio of 5:1:16, 10 wt% sodium hydroxide solution was added until the solution pH was 12, distilled at 85 ° C for 5 h, cooled to room temperature, and dried at 65 ° C and a vacuum degree of 0.6 kPa for 4.5 h to obtain modified sodium lignin sulfonate; (2) heating dimethyl methylphosphonate, deionized water, ethanol, and ammonia water to 80°C, stirring at 85 rpm for 45 min, adding tetraethyl orthosilicate, reacting for 25 h, adding silane coupling agent KH570, and reacting at 85°C for 3 h to obtain dimethyl methylphosphonate hybrid nano-silica sol; the mass ratio of dimethyl methylphosphonate, deionized water, ethanol, ammonia water, tetraethyl orthosilicate, and silane coupling agent KH570 is 5:8:4:0.6:6.5:0.03; (3) The bamboo fiber was immersed in a 4wt% sodium hydroxide solution with a mass of 13 times that of the bamboo fiber, heated to 75°C, stirred at 85rpm for 100min, allowed to stand for 12h, washed with distilled water for 9 times, filtered, and the solid was dried at 60°C and a vacuum degree of 0.6kPa for 13h. Distilled water with a mass of 35 times that of the bamboo fiber, sodium chlorite with a mass of 0.35 times that of the bamboo fiber, and glacial acetic acid with a mass of 0.28 times that of the bamboo fiber were added, heated to 75°C, allowed to stand for 65min, washed with distilled water for 8 times, and dried at 30°C for 12.5h to obtain the pretreated bamboo fiber; (4) N-methylpyrrolidone, dimethylolpropionic acid, isophorone diisocyanate and dibutyltin dilaurate were mixed in a mass ratio of 1:0.7:0.4:0.15, heated to 45°C, and reacted for 2 hours to obtain a mixed solution; cellulose nanofibers were dissolved in a 20% butanone aqueous solution with a mass fraction of 6 times the mass of the cellulose nanofibers, heated to 75°C, reacted for 2.5 hours, cooled to 40°C, and the mixed solution with a mass fraction of 2.5 times the mass of the cellulose nanofibers and a 20% butanone aqueous solution with a mass fraction of 2 times the mass of the cellulose nanofibers were added; triethylamine, react for 45 minutes, cool to 20°C, add deionized water 5 times the mass of cellulose nanofibers, stir at 1350rpm for 30 minutes to obtain cellulose nanofiber emulsion; mix anhydrous ethanol, silane coupling agent KH560 and distilled water in a mass ratio of 40:4:1, stir at 1200rpm for 20 minutes, add cellulose nanofiber emulsion 1 times the mass of silane coupling agent KH560, stir at 1500rpm for 20 minutes to obtain a modified cellulose nanofiber mixed solution; (5) spraying the modified cellulose nanofiber mixed solution evenly on the pretreated bamboo fiber at a concentration of 40 g / m2, and drying at 60°C for 5 h to obtain the modified bamboo fiber; (6) Dibutyltin dilaurate, dimethyl methylphosphonate hybrid nano-silica sol, modified sodium lignin sulfonate, and modified bamboo fiber were mixed, stirred at 85 rpm for 30 min, diphenylmethane diisocyanate was added, and stirring was continued for 2 min. The mixture was poured into a mold, allowed to stand for 75 min, demolded, and aged at 65° C. for 10 h to obtain a thermal insulation and energy-saving material for construction; the mass ratio of the dibutyltin dilaurate, dimethyl methylphosphonate hybrid nano-silica sol, modified sodium lignin sulfonate, modified bamboo fiber, and diphenylmethane diisocyanate was 1.5:14:24:5.7:24.

Citation Information

Patent Citations

  • Processing technology of bamboo fibers for fabrics

    CN106868603A

  • Preparation method of polyacrylamide weak gel

    CN108841369A